Innovation for a Sustainable Future: Boosting Circular Economy Practices in Agriculture - Vinh, Nguyen Thi Thanh; Ninh, Nguyen Van (International Journal of Innovative Research and Scientific Studies, 2025)
Circular economy practices in agriculture represent a shift toward resource-efficient, sustainable farming systems that minimize waste and environmental impact. To better understand the behavioral mechanisms underlying their adoption, this study applies the Diffusion of Innovations Theory and the Theory of Planned Behavior to examine how innovation attributes and psychological constructs shape farmers’ decisions. A quantitative survey was conducted among 367 farmers in the Hong River Delta. The model examines how innovation attributes such as relative advantage and compatibility influence farmers’ attitudes and decision-making through the mediation of TPB constructs (attitude, subjective norms, perceived behavioral control). The results show that subjective norms have a stronger effect on sustainable practice adoption (β = 0.365, p < 0.001) and economic resilience (β = 0.230, p = 0.000) than other TPB constructs. Trialability and observability negatively influence perceived control and attitude due to limited access and visibility. The study highlights the dominant role of social factors in driving behavioral change. The integration of DOI and TPB provides a comprehensive framework for understanding farmers’ adoption behavior. Social and psychological factors are central to promoting sustainable and economically resilient agriculture. Policymakers should enhance peer influence and community demonstrations while simplifying technical trials to support circular economy transitions.